Art Criticisms Versus Art Writings: The Malaysian Situation - Abdullah, Sarena (RogueArt, 2016)
Since the 1990s, the changes in Malaysia's cultural domain have been very significant. In recent years, the Malaysian art scene has become an ongoing and thriving art initiative that is constantly changing. Additionally, the advent of globalisation and cyber technologies, particularly the Internet, has influenced and directed energies in the arts and artists in very different directions. Since 2006, the prices of works of some Malaysian artists have soared with the general international demand for Asian works. Some Malaysian artists have gained international recognition, winning commissions from japanese and European museums, and being invited to participate in prestigious biennales around the world.